Niche dynamics in amphitropical desert disjunct plants: Seeking for ecological and species‐specific influences - Quiroga, Raul Emiliano; Premoli, Andrea Cecilia; Fernandez, Roberto J. (Wiley, 2020)
Numerous studies have assessed whether species niches are conserved in geographically separated regions. However, most of them were performed on invasive species, with the limitation that such species have likely not yet reached their potential distribution in the invaded region. Here we test the hypothesis of niche conservatism in the entire group of 25 amphitropical desert disjunct plant species, naturally distributed in North and South America but absent in the tropics. We also assessed the influence of ecological (intensity of biotic interactions) and species‐specific factors (dispersal ability and adaptation to stress) on species niche differentiation between the two continents.